PENGARUH PERKEMBANGAN CRYPTOCURRENCY SEBAGAI OBJEK HARTA WARISAN PERSPEKTIF ULAMA KONTEMPORER - Firdaus Fika Ananda; Irsan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the extent to which the development of cryptocurrency influences its status as an object of inheritance from the perspective of contemporary Islamic scholars. Utilizing a qualitative approach and literature review, the research explores the concept of māl in Islamic jurisprudence according to the Hanafī school and the majority of scholars (jumhūr), while assessing the eligibility of various types of cryptocurrency, such as payment tokens, utility tokens, and asset-backed tokens—as inheritable assets. The study also compares fatwas issued by different religious institutions and contemporary scholars, both those who support and those who oppose the legitimacy of cryptocurrency under Islamic law. The findings reveal two dominant viewpoints: one group strictly prohibits cryptocurrency, citing the presence of gharar (uncertainty), qimār (speculation), and the absence of underlying real assets; the other group permits its use within specific conditions, provided it has clear value, utility, and lawful ownership. This divergence directly affects the technical practices of digital estate planning and highlights the urgent need for a more comprehensive Islamic legal framework to govern crypto-assets in the context of contemporary Islamic inheritance and financial transactions.